Validation of the ACE [Albumin, CRP, and Endoscopy] Index in Acute Colitis: Analysis of the CONSTRUCT dataset - Hayley Hutchings (Journal of Crohn's and Colitis, 2024)
Background and Aims: In 2020 we reported the ACE Index in acute colitis which used biochemical and endoscopic parameters to predict steroid non-response on admission in patients with acute ulcerative colitis [UC]. We aimed to validate the ACE Index in an independent cohort. Methods: The validation cohort comprised patients screened as eligible for inclusion in the CONSTRUCT study, a prospective, randomized, placebo-controlled trial which compared the effectiveness of treatment with infliximab vs ciclosporin in patients admitted with acute UC. The CONSTRUCT cohort database was reviewed at The Edinburgh IBD Unit and the same biochemical and endoscopic variables and cut-off values as those in the derivation cohort were applied to the validation cohort. Results: In total, 800 patients were identified; 62.5% [55/88] of patients with a maximum ACE Index of 3 did not respond to intravenous [IV] steroids (positive predictive value [PPV] 62.5%, negative predictive value [NPV] 79.8%). Furthermore, 79.8% [158/198] of patients with an ACE Index of 0 responded to IV steroids [PPV 79.8%, NPV 62.5%]. Receiver operator characteristic [ROC] curve analysis produced an area under the curve [AUC] of 0.663 [p < 0.001]. Conclusions: We have now reported and externally validated the ACE Index in acute colitis in a combined cohort of over 1000 patients from across the UK. The ACE Index may be used in conjunction with clinical judgement to help identify patients admitted with active UC who are at high risk of not responding to IV steroids. Further studies are required to improve objectivity and accuracy of assessment.